Gleadovia konyakianorum (Orobanchaceae), a new species from Nagaland, India - Odyuo, N.; Roy, Dilip Kr.; Averyanov, Leonid V. (Phytotaxa, 2017)
A new species of the genus Gleadovia from Nagaland, Northeastern India, Gleadovia konyakianorum is here described and illustrated. The new species differs from its presently known congeners, such as G. banerjiana, G. mupinense and G. ruborum in having strictly 1-flowered inflorescence borne at stem apex, urceolate calyx unequally 5-lobed at apical part, white corolla, narrowly ovoid to fusiform, ca. 1 cm long anther, moderately shorter style, 0.5–0.6 cm long and in narrowly subulate, comparatively longer stigma, to 2.5 cm long. Identification key to the species of Gleadovia is given.